"Invoke at any time ...": apotropaic texts and belief in demons in the literature of the Qumran community - Fröhlich, Ida (Biblische Notizen, 2008)
Apocryphal psalms and ’sectarian’ apotropaic compositions from Qumran refer regularly to traditions about the origin and characteristic of evil spirits. A systematic elaboration of these traditions can be found in two comprehensive pseudepigraphic works, in the so-called Ethiopic book of Enoch (1En 6-11) and in the book of Jubilees, both known in extenso in Ethiopian translations. Copies of the original Aramaic version of 1Enoch and the original Hebrew version Jubilees were found in Qumran. 1Enoch and Jubilees were not only known in the community, but belonged to its core tradition and inspired many ’sectarian’ works. 1En 6-11, the story of the Watchers, is a narrative on the origin of the evil. Both, the originators (the Watchers) and the representatives of evil (the Giants) show demonic features. The rationale of the demons is impurity. 1En 6-11 is an alternative to the theology of the origin of evil in Genesis. Jubilees merges the traditions of Genesis and that of 1Enoch, adding new motives to the figure of the demonic evil who is called Mastema in Jubilees. Mastema is the head of a demonic hierarchy and a representative of both cosmic and ethical evil. Jubilees gives examples of persons who have power over evil demons. Persons who can obtain divine power and angelic help against evil are the righteous, which are owners of special knowledge. Apotropaic texts using the power of writing against demons hold the same ideas as 1Enoch and Jubilees.